Highly Emissive Lanthanide-Based 0D Metal Halide Nanocrystals for Efficient Ultraviolet Photodetector - Min, Jeong Wan; Samanta, Tuhin; Lee, Ah Young; Jung, Young Kwang; Viswanath, Noolu Srinivasa Manikanta; Kim, Yu Ri; Cho, Han Bin; Moon, Ji Yoon; Jang, Se Hyuk; Kim, Jong H.; Im, Won Bin (Small, 2024)
Recently, lanthanide-based 0D metal halides have attracted considerable attention for their applications in X-ray imaging, light-emitting diodes (LEDs), sensors, and photodetectors. Herein, lead-free 0D gadolinium-alloyed cesium cerium chloride (Gd3+-alloyed Cs3CeCl6) nanocrystals (NCs) are introduced as promising materials for optoelectronic application owing to their unique optical properties. The incorporation of Gd3+ in Cs3CeCl6 (CCC) NCs is proposed to increase the photoluminescence quantum yield (PLQY) from 57% to 96%, along with significantly enhanced phase and chemical stability. The structural analysis is performed by density functional theory (DFT) to confirm the effect of Gd3+ in Cs3Ce1-xGdxCl6 (CCGC) alloy system. Moreover, the CCGC NCs are applied as the active layer in UVPDs with different Gd3+ concentration. The excellent device performance is shown at 20% of Gd3+ in CCGC NCs with high detectivity (7.938 × 1011 Jones) and responsivity (0.195 A W−1) at -0.1 V at 310 nm. This study paves the way for the development of lanthanide-based metal halide NCs for next-generation UVPDs and other optoelectronic applications.
Keywords: Active Layer; Alloy system; Density-functional-theory; Device performance; Gadolinia; Lead-Free; Lightemitting diode; Optoelectronic applications; Photoluminescence quantum yields; Ultra-violet photodetectors; lanthanide; metal halides; nanocrystals; photodetector; photoluminescence; quantum yields